Predictors of DAPSA28 remission in patients with psoriatic arthritis initiating a first TNF inhibitor: results from 13 European registries - Linde, Louise; Ørnbjerg, Lykke M; Georgiadis, Stylianos; H Rasmussen, Simon; Lindström, Ulf; Askling, Johan; Michelsen, Brigitte; Di Giuseppe, Daniela; Wallman, Johan K; Gudbjornsson, Bjorn; Love, Thorvardur Jon; Nordström, Dan C; et al. (Rheumatology, 2024)
OBJECTIVES: In bio-naïve patients with PsA initiating a TNF inhibitor (TNFi), we aimed to identify baseline predictors of Disease Activity index for PsA in 28 joints (DAPSA28) remission (primary objective) and DAPSA28 moderate response at 6 months, as well as drug retention at 12 months across 13 European registries. METHODS: Baseline demographic and clinical characteristics were retrieved and the three outcomes investigated per registry and in pooled data, using logistic regression analyses on multiply imputed data. In the pooled cohort, selected predictors that were either consistently positive or negative across all three outcomes were defined as common predictors. RESULTS: In the pooled cohort (n = 13 369), 6-month proportions of remission, moderate response and 12-month drug retention were 25%, 34% and 63% in patients with available data (n = 6954, n = 5275 and n = 13 369, respectively). Five common baseline predictors of remission, moderate response and 12-month drug retention were identified across all three outcomes. The odds ratios (95% CIs) for DAPSA28 remission were: age, per year: 0.97 (0.96-0.98); disease duration, years (<2 years as reference): 2-3 years: 1.20 (0.89-1.60), 4-9 years: 1.42 (1.09-1.84), ≥10 years: 1.66 (1.26-2.20); men vs women: 1.85 (1.54-2.23); CRP of >10 vs ≤10 mg/l: 1.52 (1.22-1.89) and 1 mm increase in patient fatigue score: 0.99 (0.98-0.99). CONCLUSION: Baseline predictors of remission, response and adherence to TNFi therapy were identified, of which five were common for all three outcomes, indicating that the predictors emerging from our pooled cohort may be considered generalizable from country level to disease level.
Keywords: Registries; psoriatická artritida; inhibitory TNF; lidé; registrace; Female; mužské pohlaví; Arthritis, Psoriatic; Tumor Necrosis Factor Inhibitors; Male; Fatigue; imunoterapie; Immunotherapy; ženské pohlaví; únava; Humans